Soil erodibility assessment at Ibu Pejabat Polis Kontinjen (IPPK) Shah Alam, Selangor / Rohaya Alias … [et al.] - Alias, Rohaya; Bachok, Mohd. Fairuz; Mohd. Saim, Noraida; Wan Abdullah, Wan Zukri (2011)
Rapid developments of the slopes and hill tops have resulted high rates of soil erosion. Soil erosion is a continuing long term problem and has become a very serious problem in Malaysia. As the awareness on the impact of soil erosion increased, a research has been carried out to determine the soil erodibility at lbu Pejabat Polis Kontinjen (IPPK) Shah Alam, Selangor. IPPK has been chosen for the study of soil erosion since most the developments are on the hilly area. The research was carried out by physical reconnaissance around IPPK area so as to give an indication of soil erosion features presents. In addition, laboratory testing on the particle size distribution of the samples collected at the respective locations around the IPPK area were analyzed so as to establish the soil erodibility index using 'ROM' Scale method. From research finding, soil sample no. 7 from site D has the highest value of erodibility index. This site is the most critical area to soil erodibility as compared to the other sites. Hopefully, the information and research findings would assist the authorities taking action and remedial works should be done to control soil erosion problem at this area.